Managing transportation challenges in selected southeast asia countries: comparison of policies, framework and components / Nabihah Kamarudin, Gobi Krishna Sinniah and Zuhra Junaida Mohamad Husny Hamid - Kamarudin, Nabihah; Sinniah, Gobi Krishna; Mohamad Husny Hamid, Zuhra Junaida (Universiti Teknologi MARA, Perak, 2022)
Urbanisation is often correlated with economic growth and expansion of countries, but previous studies show that it has caused environmental degradation in the countries. While many countries are striving to develop and aim to achieve sustainability, some countries are facing unmanageable issues related with urbanization. In Southeast Asia, Singapore as a developed country tends to have small emission of carbon while Indonesia and Malaysia as developing countries are the total opposite. This paper aims to discuss how Southeast Asia developed and developing countries manage the challenges of carbon emission that was caused by transport through policies and the implementation. Several countries are used as case studies: Malaysia, Indonesia and Singapore. This paper also summarizes and analyzes using Cashore and Howlett Method (2007) between these two groups of countries, given the implementation on managing the environmental issues of these countries are different. The method also calibrated with A-S-I approach, known as Avoid, Shift and Improve to analyse the implementations that can be used. Finally, this paper provides some alternatives for urban planners to develop resilient countries that could benefit the well-being of the society and promote healthier countries. The findings of this study show that developed countries have better implementation of their policies through taxes, so that people would travel by public transport for shorter distances.